Holistic view of biological nitrogen fixation and phosphorus mobilization in Azotobacter chroococcum NCIMB 8003 - Biełło, Karolina A.; Lucena, Carlos; López-Tenllado, Francisco J.; Hidalgo-Carrillo, Jesús; Rodríguez-Caballero, Gema; Cabello, Purificación; Sáez, Lara P.; Luque-Almagro, Víctor; Roldán, María Dolores; Moreno-Vivián, Conrado; Olaya-Abril, Alfonso (Frontiers in Microbiology, 2023)
Nitrogen (N) and phosphorus (P) deficiencies are two of the most agronomic problems that cause significant decrease in crop yield and quality. N and P chemical fertilizers are widely used in current agriculture, causing environmental problems and increasing production costs. Therefore, the development of alternative strategies to reduce the use of chemical fertilizers while maintaining N and P inputs are being investigated. Although dinitrogen is an abundant gas in the atmosphere, it requires biological nitrogen fixation (BNF) to be transformed into ammonium, a nitrogen source assimilable by living organisms. This process is bioenergetically expensive and, therefore, highly regulated. Factors like availability of other essential elements, as phosphorus, strongly influence BNF. However, the molecular mechanisms of these interactions are unclear. In this work, a physiological characterization of BNF and phosphorus mobilization (PM) from an insoluble form (Ca3(PO4)2) in Azotobacter chroococcum NCIMB 8003 was carried out. These processes were analyzed by quantitative proteomics in order to detect their molecular requirements and interactions. BNF led to a metabolic change beyond the proteins strictly necessary to carry out the process, including the metabolism related to other elements, like phosphorus. Also, changes in cell mobility, heme group synthesis and oxidative stress responses were observed. This study also revealed two phosphatases that seem to have the main role in PM, an exopolyphosphatase and a non-specific alkaline phosphatase PhoX. When both BNF and PM processes take place simultaneously, the synthesis of nitrogenous bases and L-methionine were also affected. Thus, although the interdependence is still unknown, possible biotechnological applications of these processes should take into account the indicated factors.